Moore-Penrose inverse of an invertible infinite matrix - Sivakumar, K. C. (Linear & multilinear algebra, 2006)
In this article we show that, contrary to finite matrices (with real or complex entries) an invertible infinite matrix V could have a Moore-Penrose inverse that is not a classical inverse of V. This also answers a recent open problem on infinite matrices.